El cuerpo ¿medio o mediación? Reflexiones sobre el cuerpo en el campo de la comunicación (2006)
ABSTRACT: The intention that locks up this essay is the one to put into play a joint body-culture-communication, that offers access routes to the academic field of the last one and causes a glance towards the construction of the field to discipline of the Physical Education. For the thematic itinerary I have started from generating questions that orient the speech: why the body must participate in the field of the communication? (first moment); which would be the category of its presence in the field, this is: guest in quality of what? (second moment); it is the body mean or mediation? (third moment). The frame of the test is conformed in reason to pertinent elements to the same one, the conceptual gradients that overflow the originating costs of the thinkers of the own field and to the perspective of analysis that offers the text «from means to the mediations», mentioned repeatedly.